Efficient diels-alder reaction of 1,2-benzoquinones with arynes and its utility in one-pot reactions - Kaicharla, Trinadh; Bhojgude, Sachin Suresh; Biju, Akkattu T. (Organic Letters, 2012)
A new protocol for the efficient Diels–Alder reaction of 1,2-benzoquinones with arynes is reported. The aryne generated by the fluoride-induced 1,2-elimination of 2-(trimethylsilyl)aryl triflates undergoes a facile Diels–Alder reaction with 1,2-benzoquinones, affording the dioxobenzobicyclooctadienes in moderate to excellent yields. In addition, this methodology has been applied to the one-pot synthesis of benzoquinoxalinobarrelene and naphthalene derivatives.